A new thin silicon microneedle with an embedded microchannel for deep brain drug infusion - Lee, Hyunjoo J.; Son, Yoojin; Kim, Dohee; Kim, Yun Kyung; Choi, Nakwon; Yoon, Eui-Sung; Cho, Il-Joo (ELSEVIER SCIENCE SA, 2015)
We present the implementation of a new thin silicon microneedle for deep brain drug infusion implemented using a fabrication technology called glass cover on silicon technology (GCoS) that embeds microchannels in silicon substrate. The embedded microchannels are formed by anodically bonding a glass wafer to a silicon wafer with cavities, reflowing glass to partially cover the top of the cavity, and removing the unwanted glass above the silicon substrate. Because no dielectric sealing process is required, long microchannels in mm range can be readily fabricated using GCoS and there is no restriction on the cross-sectional area or shape. In addition, the silicon substrate is directly available for further integrated circuit (IC) processing and consists of embedded microchannels that are transparent from top through the glass. Using GCoS, we have successfully implemented a microneedle designed for drug infusion with point targeting accuracy as well as less damage for small animal experiments. The fabricated microneedles were 5.3 mm in length and as small as 40 mu m in thickness and 70 mu m in width. Fluidic characterization with a pressure-driven injection system showed linearly decreasing flow rates ranging from 100 to < 50 nl/min. This linearity of the flow rates to input pressure confirms precise control of the low flow rates, which is important in injecting small quantity of drugs. After we verify successful infusions of trypan blue with our microneedles into both 0.9% w/v agarose gel and sacrificed mouse brain, we demonstrate the possibility of drug infusions with not only precise targeting capability but also less brain damage by infusing dyes in vivo followed by immunohistochemistry (IHC). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: DELIVERY